Pemanfaatan Limbah Kulit Buah sebagai Ekoenzim (Pupuk Organik Cair) - Sofyan, Adnan; Idris Abd. Rachman; Asrul Dedy A. Hasan; Gunawan Hartono4 (Program Studi Kehutanan, Universitas Khairun, 2024)
ABSTRACT Fruit peel waste is an organic waste material which is solid waste which, if left untreated, can cause an unpleasant odor and disrupt the comfort of the surrounding environment. Many people have used waste from fruit peels, such as making compost or organic fertilizer and so on. One use of waste from fruit peels is to use it by making ecoenzymes. The enzymes produced from fermentation are a waste management method that utilizes kitchen scraps to produce something very useful. Ecoenzymes can be used as multifunctional liquids and their applications include households, agriculture, animal husbandry, and even in the health sector. The fruit peel waste used in this research was pineapple, papaya, orange, mango and watermelon. The aim of this activity is to improve the skills of farming groups in making ecoenzymes by using pineapple, papaya, orange, mango and watermelon peels which are applied to mustard plants as liquid fertilizer. The result of this activity is that the training participants have relatively the same perception and understanding and are able to independently make ecoenzymes and apply them to soil, plants and the environment in general. Keywords: Ecoenzymes, pineapple, papaya, orange, mango, watermelon